International Participation in Quality Assurance within the European Higher Education Area - Adriana Daniela Șerban (University Babes-Bolyai, 2018)
At the Berlin Ministerial Meeting in September 2003, ministers with responsibility for higher education tasked the Bologna Follow-up Group to undertake a stocktaking exercise on the progress made in three priority action lines - quality assurance, the two-cycle degree system and recognition of degrees and periods of study. The international participation and networking in quality assurance within the European Higher Education Area (EHEA) was established as one of the aspects that needs to be monitored. The group presented detailed reports at conferences held in Bergen (May 2005), London (May 2007), Leuven (April 2009), Bucharest (April 2012) and Yerevan (May 2015). The purpose of this paper is to present the comparative results of the five stocktaking exercises regarding the international participation within EHEA and to provide information about how the Romanian higher education system has faced this challenge.